This thing of darkness : Eisenstein's Ivan the Terrible in Stalin's Russia - Neuberger, Joan, 1953- (Cornell University Press, 2019)
"Eisenstein's diaries and production notebooks show that he carefully planned Ivan the Terrible to be a devastating critique of Stalinism, a profound study of the tragedy of absolute power, and a wildly innovative use of montage, all wrapped inside a narrative that would receive Stalin's approval"-- Provided by publisher.
Keywords: Ivan Groznyĭ (Motion picture); Eisenstein, Sergei, -- 1898-1948 -- Criticism and interpretation.; Stalin, Joseph, -- 1878-1953 -- Influence.; Ivan -- IV, -- Czar of Russia, -- 1530-1584 -- In motion pictures.; Eisenstein, Sergei, -- 1898-1948; Ivan -- IV, -- Czar of Russia, -- 1530-1584; Stalin, Joseph, -- 1878-1953; Motion pictures -- Political aspects -- Soviet Union.; Cinéma -- Aspect politique -- URSS.; PERFORMING ARTS -- Reference.; HISTORY -- Europe -- Russia & the Former Soviet Union.; Influence (Literary, artistic, etc.); Motion pictures; Motion pictures -- Political aspects; Soviet Union; Criticism, interpretation, etc.